2016
DOI: 10.1016/j.foodqual.2016.05.014
|View full text |Cite
|
Sign up to set email alerts
|

What are we eating? Consumer information requirement within a workplace canteen

Abstract: 1The workplace is a captive environment where the overall contribution of the meal served could be 2 an important element of the overall diet. Despite growing demand little information is available to 3 aid healthy dish selection. 4This study identifies information valued by consumers in the UK, Greece, Denmark and France using 5 best-worst scaling. Value for Money, Nutrition and Naturalness are key elements of information that 6 consumers require to be able to make a conscious decision about dish selection in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 43 publications
2
31
0
Order By: Relevance
“…In this regard, the findings support the work of Chan et al (2013) and Price et al (2016) in terms of the importance of factors such as provenance, allergen information, animal welfare, health and freshness of food.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In this regard, the findings support the work of Chan et al (2013) and Price et al (2016) in terms of the importance of factors such as provenance, allergen information, animal welfare, health and freshness of food.…”
Section: Discussionsupporting
confidence: 88%
“…Consequently, consumers are increasingly seeking information about the foods they buy (Lusk and Marette 2012). Chan et al (2013) and Price et al (2016) have identified the kinds of information that consumers are seeking when selecting food items especially out of the home.…”
Section: Literature Review: Health Consciousness and The Need For Infmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, consumer consultations using qualitative and quantitative methods were conducted to understand the information they would like from the app (Price et al . ; Bray et al . 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, in the work of Price et al . (), eight focus groups of workplace canteen users ( n = 40) were conducted, two groups from four European countries (Denmark, France, Greece and the UK), to understand which factors influence their food‐based decisions in a canteen setting and their preferred formats of food information provision ( e.g . health logos, traffic light labelling).…”
Section: Methodsmentioning
confidence: 99%